Impact of age and sex on primary preventive treatment for cardiovascular disease in the West Midlands, UK: cross sectional study. (12th July 2012) - Sheppard, J P; Singh, S; Fletcher, K; McManus, R J; Mant, J
Abstract : Objectives To establish the impact of age and sex on primary preventive treatment for cardiovascular disease in a typical primary care population. Design Cross sectional study of anonymised patient records. Participants All 41 250 records of patients aged ≥40 registered at 19 general practices in the West Midlands, United Kingdom, were extracted and analysed. Main outcome measures Patients' demographics, risk factors for cardiovascular disease (blood pressure, total cholesterol concentration), and prescriptions for primary preventive drugs were extracted from patients' records. Patients were subdivided into five year age bands up to 85 (patients aged ≥85 were analysed as one group) and prescribing trends across the population were assessed by estimating the proportion of patients prescribed with antihypertensive drug or statin drug, or both, in each group. Results Of the 41 250 records screened in this study, 36 679 (89%) patients did not have a history of cardiovascular disease and therefore could be considered for primary preventive treatment. The proportion receiving antihypertensive drugs increased with age (from 5% (378/6978) aged 40-44 to 57% (621/1092) aged ≥85) as did the proportion taking statins up to the age of 74 (from 3% (201/6978) aged 40-44 to 29% (675/2367) aged 70-74). In those aged 75 and above, the odds of a receiving prescription for a statin (relative to the 40-44 age group) decreased with every five year increment in age (odds ratio 12.9 (95% confidence interval 10.8 to 15.3) at age 75-79 to 5.7 (4.6 to 7.2) at age ≥85; P<0.001). There were no consistent differences in prescribing trends by sex. Conclusions Previously described undertreatment of women in secondary prevention of cardiovascular disease was not observed for primary prevention. Low use of statins in older people highlights the need for a stronger evidence base and clearer guidelines for people aged over 75.